Hennes & Mauritz (H&M). standing up for human rights in China / A : - Derr, Timothy, (SAGE business cases., 2021)
Following reports of forced labor in its supply chain, fast fashion merchandiser H&M stopped sourcing cotton from China's Xinjiang region, the site of alleged genocide. After Western sanctions sparked nationalist outrage, China retaliated by boycotting H&M. Will H&M continue defending human rights or choose to preserve the growing Chinese market?